Estadistas, Caciques y Caudillos - Martínez Assad, Carlos (UNAM, 1988)
Investigaciones acerca del ejercicio del poder de los siguientes políticos: Gordiano Guzmán, Francisco Leyva, Adolfo de la Huerta, Obregón, Elías Calles, Portes Gil, Lázaro Cárdenas, Avila Camacho, Emiliano Zapata, Eulogio Gillow, Guillermo Meixueiro, Cándido Aguilar, Carlos Greene, etc.